SOFTWARE TESTING - Nayak, Pooja; Mudgal, Sahil; Wason, Rajat (IJRDO -Journal of Computer Science Engineering, 2015)
Software testing is any activity aimed at evaluating an attribute or capability of a program or system and determining that it meets its required results. Testing is more than just debugging. The purpose of testing can be quality assurance, verification and validation, or reliability estimation. Testing can be used as a generic metric as well. Correctness testing and reliability testing are two major areas of testing. Software testing is a trade-off between budget, time and quality.This Paper include all the types of testing and the need of testing and also discuss about the tools of the testing